Myasthenia gravis patients with anti-MuSK antibodies - Žagar, Marija; Vranješ, Davorka; Šoštarko, Marija; Vogrinc, Željka; Bilić, Ervina; Trbojević-Čepe, Milica (2009)
Abstract: In myasthenia gravis (MG) patients without detectable anti-acetylcholine receptor (anti-AChR) antibody, referred to as seronegative myasthenia gravis patients, there is a variable proportion of patients with antibodies against the muscle-specific kinase (MuSK). MuSK antibodies were found in 8 (29.6%) of our 27 patients with generalized MG without anti-AChR antibodies. All these patients were female. The age at the onset ranged from 22 to 38 years. All patients had ocular and bulbar symptoms, and two patients also had generalized limb weakness. Two patients had pure ocular symptoms for 7 or 8 years before the development of bulbar symptoms. All anti-MuSK positive patients were treated with immunosuppressive drugs, three received plasmapheresis and one patient required mechanical ventilation. Our results are consistent with other literature reports
Bibliografija: 16 jed
Sažetak
Keywords: Miastenija gravis -- Specifična mišićna kinaza -- Acetilkolinski receptori